Formation and Control of Zero‐Field Antiskyrmions in Confining Geometries. Issue 28 (17th August 2022) - Peng, Licong; Iakoubovskii, Konstantin V.; Karube, Kosuke; Taguchi, Yasujiro; Tokura, Yoshinori; Yu, Xiuzhen
Abstract: Magnetic skyrmions and antiskyrmions have attracted much interest owing to their topological features and spintronic functionalities. In contrast to skyrmions, the generation of antiskyrmions relies on tunning both the magnitude and direction of the external magnetic field. Here, it is reported that antiskyrmions can be efficiently created via quenching and robustly persist at zero field in the Fe1.9 Ni0.9 Pd0.2 P magnet with the S 4 ‐symmetry. It is demonstrated that well‐ordered antiskyrmions form in a square lattice in a confining micrometer‐scale square geometry, while the antiskyrmion lattice distorts in triangular, circular, or rotated‐square geometry; the distortion depends on the relative configuration between sample edges and the two q ‐vectors arising from the anisotropic Dzyaloshinskii–Moriya interaction, in good agreement with micromagnetic simulations. It is also characterized transformations from antiskyrmions to skyrmions and nontopological bubbles at different directions and values of external field. These results demonstrate a roadmap for generating and controlling antiskyrmions in a confining geometry. Abstract : Magnetic antiskyrmions have been investigated in noncentrosymmetric magnets. The effect of geometry on their formation and stability is crucial for understanding the intrinsic properties of antiskyrmions, yet it has rarely been studied. Here, the authors demonstrate the formation and control of confined zero‐field antiskyrmions and the impact of sample geometry on the lattice form, revealing the inter‐particle and particle‐edge interactions.